Milipitas Ranch, Hacienda [copy print], September 2, 1929 (1929)
Copy print of a photograph of William Randolph Hearst's Milpitas Ranch in Monterey County. The original photograph was taken in 1929. The verso reads: '8084; Farm Buildings; Milpitas Ranch; Property of W.R. Hearst Sept. 2, 1929'.